Lactate as an Astroglial Signal Augmenting Aerobic Glycolysis and Lipid Metabolism - Horvat, Anemari; Zorec, Robert; Vardjan, Nina (Frontiers in Physiology, 2021)
Astrocytes, heterogeneous neuroglial cells, contribute to metabolic homeostasis in the brain by providing energy substrates to neurons. In contrast to predominantly oxidative neurons, astrocytes are considered primarily as glycolytic cells. They take up glucose from the circulation and, in the process of aerobic glycolysis (despite the normal oxygen levels), produce L-lactate, which is then released into the extracellular space via lactate transporters and possibly channels. Astroglial L-lactate can enter neurons, where it is used as a metabolic substrate, or exit the brain via the circulation. Recently, L-lactate has also been considered to be a signaling molecule in the brain, but the mechanisms of L-lactate signaling and how this contributes to brain function remain to be fully elucidated. Here, we provide an overview of L-lactate signaling mechanisms in the brain and present novel insights into the mechanisms of L-lactate signaling via G-protein coupled receptors (GPCRs) with the focus on astrocytes. We discuss how increased extracellular L-lactate upregulates cAMP production in astrocytes, most likely via L-lactate-sensitive Gs-protein coupled GPCRs. This activates aerobic glycolysis, enhancing L-lactate production and accumulation of lipid droplets, suggesting that L-lactate augments its own production in astrocytes (i.e., metabolic excitability) to provide more L-lactate for neurons and that astrocytes in conditions of increased extracellular L-lactate switch to lipid metabolism.